Experience of using Fenokit in infants with atopic dermatitis - L.V. Besh; O.I. Matsyura; Z.L. Slyuzar (Zaslavsky O.Yu., 2019)
Background. About 35 % of world population request for medical support for clinical allergy symptoms annually. Its first sign as usual is food allergy, which is diagnosed in early childhood and mainly manifests by atopic dermatitis. On the pages of special literature, the issues of terminology, clinical features and treatment of atopic dermatitis are debated a lot. In particular, the use of antihistamines for the treatment of this pathology in infants is interpreted ambiguously. The purpose is to presents our experience of using drug Fenokit. Materials and methods. The study group enrolled 50 children with atopic dermatitis (mild to moderate course) aged from 1 and 18 months old. Exclusion criteria were as follows: somatic and neurological diseases, a severe form of atopic dermatitis. The disease was monitored based on an assessment of the disease severity by the SCORAD index; severity of itching; the frequency of adverse events and side effects registered by the doctor; quality of life of patients. Results. The follow-up of children within a month revealed positive dynamics of clinical symptoms (decrease of SCORAD index from 29.2 to 3.5; itching regression from 6.4 to 0.3) and significant improvement of quality of life of patients (from 19.1 to 4.2). Four children dropped out of the study because they need additional drugs for treatment (topical corticosteroids). Three patients developed side effects (episodic nausea, irritability), but they did not require discontinuation of the drug. Conclusions. Antihistamine Fenokit makes it possible to control the manifestations of atopic dermatitis in infants effectively.